2015
DOI: 10.1016/j.ces.2015.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a structural mechanics model to predict the effect of inserts in the bed support of chromatographic columns

Abstract: Inserts are placed within chromatography columns to enhance wall support. The impact of column inserts is captured by structural mechanics models.Simulations are shown to be in good agreement with experimental data. The model helps selecting dimensions of inserts to increase column linear velocity. a b s t r a c tCell culture titres are expected to increase still further over the forthcoming years. This imposes challenges for downstream processing including the potential need to use larger volumes of chromatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…McCarthy et al [29] and Lovregio et al [30] showed that porosity values of spheres confined in annular and cylindrical cells, respectively, obtained through DEM and experimental methods can agree well quantitatively. Meanwhile, Gerontas et al [31] successfully developed a structural mechanics model of resin compression in a liquid chromatography column, which used the finite element method to simulate the effect of wall support inside the column on the process in agreement with the experimental data of Lan et al [20]. This consequently allowed the model to predict previously untested scenarios, thereby providing a convenient case study method.…”
Section: Romanmentioning
confidence: 99%
“…McCarthy et al [29] and Lovregio et al [30] showed that porosity values of spheres confined in annular and cylindrical cells, respectively, obtained through DEM and experimental methods can agree well quantitatively. Meanwhile, Gerontas et al [31] successfully developed a structural mechanics model of resin compression in a liquid chromatography column, which used the finite element method to simulate the effect of wall support inside the column on the process in agreement with the experimental data of Lan et al [20]. This consequently allowed the model to predict previously untested scenarios, thereby providing a convenient case study method.…”
Section: Romanmentioning
confidence: 99%
“…Chromatography column scale-up typically involves increasing the diameter of the column to process a higher quantity of load at a constant bed height and flow velocity (Carta & Jungbauer, 2010). The diameters of manufacturing scale columns can go above 1 m with corresponding aspect ratios >5 (Gerontas, Lan, Micheletti, & Titchener-Hooker, 2015). Such changes in the column aspect ratio increases media compression and destabilizes the bed due to the loss of wall support and pressure drop (Stickel & Fotopoulos, 2001).…”
Section: Column Aspect Ratiomentioning
confidence: 99%
“…Compared with that of the Mag gel-packed column, the pressure drop of the gel-packed column was larger because of the smaller deformation of Mag gel relative to that of the reference gel in the column. This is because magnetite in the gel particles disturbed the free deformation at the contacting surfaces of the gel particles, resulting in a smaller pressure drop [6,14].…”
Section: Permeation Of Water Through Mag Gelmentioning
confidence: 99%